The ethics of astrobiology: Humanity’s place in the cosmos and the extinction problem - Lo Sapio, Luca (Frontiers in Astronomy and Space Sciences, 2022)
Western philosophy has always stressed the importance of understanding the very nature of the universe and the relationship between man and the cosmos. Nowadays, astrobiology sheds light on that issue through a set of empirical data. Also, the Fermi Paradox and the rare Earth hypothesis could offer a suitable ground to interpret properly the proofs emerging from space exploration and direct and indirect observations of astronomers, that is “we are likely the only intelligent species within the universe”. From this follows that maybe we are confronting with a cosmic bet. We’d better wager on our cosmic importance as a species, otherwise the loss could be immense: the disappearance of the only species through which the universe enabled itself to understand its own secrets and cosmic treasures